2021
DOI: 10.3390/pathogens10081042
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Circulation of SARS-CoV-2 Variants by Genomic Analysis of Wastewater in Marseille, South-East France

Abstract: The monitoring of SARS-CoV-2 RNA in sewage has been proposed as a simple and unbiased means of assessing epidemic evolution and the efficiency of the COVID-19 control measures. The past year has been marked by the emergence of variants that have led to a succession of epidemic waves. It thus appears that monitoring the presence of SARS-CoV-2 in wastewater alone is insufficient, and it may be important in the future to also monitor the evolution of these variants. We used a real-time RT-PCR screening test for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Also, SARS-CoV-2 VOCs have been detected in sewage (pango lineage B.1.1.7 and P.1), suggesting that tracking SARS-CoV-2 variants and their abundance in sewersheds could provide an early warning system for the emergence or spread of more infectious or virulent strains in the community. More recently, SARS-CoV-2 VOCs and VOIs were identified in wastewater samples matching those found in clinical isolates from the same time periods (Ai et al, 2021 ; Avgeris et al, 2021 ; Carcereny et al, 2021 ; Gregory et al, 2021 ; Heijnen et al, 2021 ; La Rosa et al, 2021c ; Lee et al, 2021 ; Mishra et al, 2021 ; Rios et al, 2021 ; Swift et al, 2021 ; Wurtz et al, 2021 ; Yaniv et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…Also, SARS-CoV-2 VOCs have been detected in sewage (pango lineage B.1.1.7 and P.1), suggesting that tracking SARS-CoV-2 variants and their abundance in sewersheds could provide an early warning system for the emergence or spread of more infectious or virulent strains in the community. More recently, SARS-CoV-2 VOCs and VOIs were identified in wastewater samples matching those found in clinical isolates from the same time periods (Ai et al, 2021 ; Avgeris et al, 2021 ; Carcereny et al, 2021 ; Gregory et al, 2021 ; Heijnen et al, 2021 ; La Rosa et al, 2021c ; Lee et al, 2021 ; Mishra et al, 2021 ; Rios et al, 2021 ; Swift et al, 2021 ; Wurtz et al, 2021 ; Yaniv et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…Reads of wastewater samples were analyzed as previously described [27]. Briefly, reads from pool1 and pool2 provided by the ARTIC procedure were mapped together against the Wuhan-Hu-1 SARS-CoV-2 isolate genome (GenBank accession number NC_045512.2) using the CLC genomics softwarev7.5 (Qiagen Digital Insights, Germany) with the default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…After the first report of the detection of SARS-CoV-2 in wastewater by Medema et al in Netherlands [10], detection and monitoring in wastewater samples have been reported in many countries [11][12][13][14]. A few studies have performed SARS-CoV-2 genome sequencing from sewage to identify viral genotypes circulating in a community and study genetic diversity [14][15][16][17][18][19]. Some of them showed congruence bewteen variants found in clinical isolates during the same period, while others identified genotypes not yet reported in clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have demonstrated that SARS-CoV-2 RNA sequencing from wastewater could help to understand the city- or country-scale circulation of SARS-CoV-2 variants ( Nemudryi et al, 2020 ; Agrawal et al, 2021 ; Bar-Or et al, 2021 ; Crits-Christoph et al, 2021 ; Fontenele et al, 2021 ; Izquierdo-Lara et al, 2021 ; Jahn et al, 2021 ; Prado et al, 2021 ; Rouchka et al, 2021 ; Rubio-Acero et al, 2021 ; Wilton et al, 2021 ). SARS-CoV-2 WGS in sewage was conducted using multiplex PCR panels combined mostly with Illumina sequencing ( Ai et al, 2021 ; Bar-Or et al, 2021 ; Fontenele et al, 2021 ; Hillary et al, 2021 ; Izquierdo-Lara et al, 2021 ; Jahn et al, 2021 ; Mondal et al, 2021 ; Prado et al, 2021 ; Rouchka et al, 2021 ; Rubio-Acero et al, 2021 ; Wurtz et al, 2021 ), and more rarely with Oxford Nanopore Technology ( Nemudryi et al, 2020 ; Izquierdo-Lara et al, 2021 ; Rios et al, 2021 ). Here, we aimed to adapt a sequencing technique using the widely used and frequently updated ARTIC-400 panel of primers ( Tyson et al, 2020 ) and Oxford Nanopore Technology (ONT), initially designed for clinical samples, to apply it to the challenging wastewater matrix.…”
Section: Introductionmentioning
confidence: 99%